36-4x+6=

Simple and best practice solution for 36-4x+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36-4x+6= equation:


Simplifying
36 + -4x + 6 = 0

Reorder the terms:
36 + 6 + -4x = 0

Combine like terms: 36 + 6 = 42
42 + -4x = 0

Solving
42 + -4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -4x = 0 + -42

Combine like terms: 42 + -42 = 0
0 + -4x = 0 + -42
-4x = 0 + -42

Combine like terms: 0 + -42 = -42
-4x = -42

Divide each side by '-4'.
x = 10.5

Simplifying
x = 10.5

See similar equations:

| -6x+-px=-z+2 | | 10x-3=-82 | | 3/4(g+7)=15 | | 48x^2-56x-24=0 | | -3(m-1)+4m=-8+9+4m | | -17-2=3+4x+5 | | 3(4z-8)=12 | | 4(v-1)=-9v+9 | | 6z-3z+5-4=3z-5+4 | | -2(d+6)-3(4d-2)=22 | | 4x-8=11y-1 | | p=5/9*350000 | | -4(x-4)=28+8x | | 2g-12=16-10h | | 13.50/3 | | -45-5+2b=10 | | 175m-75m-53625=55000-175m | | -12x-3x=-8 | | Z=6x+px+2 | | 4x-45=7(x-9) | | -(4-6n)=n+11 | | B-1/2=b/3+7 | | ((7x+6)(2x+10))/((6x+2)(7x+5)) | | y=6/7x-2 | | -7+14k-13+-(-5k)+3= | | x/-8=-1-(-3) | | 3x=3(8-7x) | | 20.5=(w/3600)(703) | | 22-8x=-5(5x-1) | | -2(-3x+3y)=-2(-27) | | 3xy+3x=6 | | (11x)/6+2/3=2x |

Equations solver categories